Systematic Cloning of Treponema pallidum Open Reading Frames for Protein Expression and Antigen Discovery - McKevitt, Matthew (Cold Spring Harbor Laboratory Press, 2003)
A topoisomerase-based method was used to clone PCR products encoding 991 of the 1041 open reading frames identified in the genome sequence of the bacterium that causes syphilis, Treponema pallidum subsp. pallidum. Cloning the open reading frames into the univector plasmid system permitted the rapid conversion of the original clone set to other functional vectors containing a variety of promoters or tag sequences. A computational prediction of signal sequences identified 248 T. pallidum proteins that are potentially secreted from the cell. These clones were systematically converted into vectors designed to express the encoded proteins as glutathione-S-transferase fusion proteins. To test the potential of the clone set for novel antigen discovery, 85 of these fusion proteins were expressed from Escherichia coli, partially purified, and tested for antigenicity by using sera from rabbits infected with T. pallidum. Twelve of the 85 proteins bound significant levels of antibody. Of these 12 proteins, seven had previously been identified as T. pallidum antigens, and the remaining five represent novel antigens. These results demonstrate the potential of the T. pallidum clone set for antigen discovery and, more generally, for advancing the biology of this enigmatic spirochete.